1, 1-Dibromoalkenes as versatile reagents to a transition metal-free and stereoselective synthesis of (E)-1-bromo-1-selenoalkenes and ketene selenoacetals. Issue 37 (14th September 2016) - Webber, Rodrigo; Peglow, Thiago J.; Nobre, Patrick C.; Barcellos, Angelita M.; Roehrs, Juliano A.; Schumacher, Ricardo F.; Perin, Gelson
Graphical abstract: Highlights: 1, 1-Dibromoalkenes as versatile reagents to synthesis of selenoalkenes. Metal-free and selective method for the synthesis of ( E )-1-bromo-1-selenoalkenes. Metal-free and selective method for the synthesis of ketene selenoacetals. Abstract: We describe here a metal-free and selective method for the synthesis of ( E )-1-bromo-1-seleno alkenes and ketene selenoacetals by a stoichiometric and temperature-controlled reaction. These protocols employ a diverse array of 1, 1-dibromoalkenes and different diaryl diselenides to afford the corresponding products in good yields and in a short reaction time.